Effect of inulin and oligofructose on the physicochemical, microbiological and sensory characteristics of symbiotic dairy beverages - Fornelli, Anderson Rodrigo; Bandiera, Nataly Simões; Costa, Marcela De Rezende; De Souza, Cínthia Hoch Batista; De Santana, Elsa Helena Walter; Sivieri, Kátia [UNESP]; Aragon-Alegro, Lina Casale (Universidade Estadual de Londrina, 2014)
The aim of this study was to verify the effect of inulin and oligofructose on the physicochemical, microbiological and sensory characteristics of symbiotic dairy beverages. Four formulations were made: 1) a control (C); 2) a sample with added Lactobacillus paracasei (P); 3) a sample with added L. paracasei and inulin (PI); and 4) a sample with added L. paracasei and oligofructose (PO). The probiotic population, pH, and acidity of the products were evaluated once a week for 21 days while refrigerated (5±1°C). Possible contaminating microorganisms (coliforms, E. coli, and Salmonella spp.) were investigated after three days of storage. Sensorial acceptance and purchase intention were evaluated seven days after manufacture. Dairy beverages presented with L. paracasei populations above 8.50 log CFU/mL during the whole storage period. Significantly (p<0.05) lower pH values were observed in P and PI, and higher acidity values were found in all formulations throughout storage. The dairy beverages were considered to be a promising matrix for the probiotic microorganism L. paracasei. The prebiotic additions (inulin and oligofructose) did not interfere with the overall acceptance and intention to purchase the beverages.
Keywords: Lactobacillus paracasei; Prebiotics; Probiotics; Shelf life; Whey